The design of reflective tasks for the preparation of student teachers - Viàfara, John Jairo (Colombian Applied Linguistics Journal, 2005)
The preparation of student-teachers to face the beginning in their profession requires from us, teacher educators, enriching discussions to share what we know and to build more solid grounds in our area. On the following pages, I describe how, in the specifi c context of a public university, I have designed and implemented a set of tasks within a refl ective framework to support student- teachersʼ learning in their practicum. In this regard, a detailed explanation of how journal writing, conferences, focused refl ection on tasks and responses to observation notes is included. Likewise, the experience of a student teacher working with tasks to solve a diffi culty in the practicum, contributes to illustrate how refl ective exercises support her development.